Tumor-acidity and bioorthogonal chemistry-mediated construction and deconstruction of drug depots for ferroptosis under normoxia and hypoxia. (1st April 2022) - Zhou, Jielian; Wang, Kewei; Jiang, Maolin; Li, Jisi; Yuan, Youyong
Abstract: Mounting evidence shows that tumor hypoxia stress promotes tumor invasion and metastasis and induces therapeutic resistance. Oxygen-independent Fenton reaction, which refers to the iron-catalyzed conversion of endogenous hydrogen peroxide (H2 O2 ) to hydroxyl radical (·OH), has been designed for ferroptosis therapy. Nevertheless, the treatment efficiency is compromised by limited H2 O2 content and limited tumor retention and penetration of nanoparticles. Herein, we designed a tumor-acidity and bioorthogonal chemistry mediated construction and deconstruction of drug depots for tumor ferroptosis under normoxia and hypoxia. Briefly, the dendritic poly(amidoamine) (PAMAM, G4) was modified using cinnamaldehyde (CA) to deplete GSH and increase H2 O2 levels, and ferrocene (Ferr) served as Fenton reaction catalyst to generate PFC. Subsequently, PFC was modified with maleic acid amide with slow pH-response rate and poly(2-azepane ethyl methacrylate) (PAEMA) with rapid pH-response rate, accompanied with highly efficient bioorthogonal chemistry to construct and deconstruct drug depots for enhanced tumor retention and penetration. The small-sized PFC potentially induced H2 O2 self-supplied ferroptosis under normoxia and hypoxia. In sum, this work utilizes two tumoral acidity-responsive groups with different response rates and highly efficient bioorthogonal click chemistry, which paves a way for ferroptosis and provides a general drug delivery strategy with enhanced tumor retention and penetration. Statement of significance: Oxygen independent Fenton reaction refers to the conversion of endogenous H2 O2 to ·OH which has been designed for ferroptosis therapy. Nevertheless, limited H2 O2 level and abundant GSH in tumor cells could both compromise the treatment efficiency. Herein, we developed a tumor-acidity and bioorthogonal chemistry mediated construction and deconstruction of drug depots, which elevate the intracellular H2 O2 level and deplete GSH for tumor ferroptosis under normoxia and hypoxia microenvironment. This work utilizes two tumoral acidity response groups with different response rates and highly efficient bioorthogonal click reactions, which paves a way for tumor cell ferroptosis and provides a general drug delivery strategy for enhanced tumor accumulation and penetration. Graphical abstract: Image, graphical abstract